Analysis of WISC-III results based on Lithuanian children representative sample - Gintilienė, Gražina; Černiauskaitė, Dovilė; Girdzijauskienė, Sigita; Dragūnevičienė, Rūta (Psichologija, 1999)
The main goal of the WISC-III Lithuanian study was to compare the UK standardised sample with a Lithuanian representative sample, to explore whether there are any differences between the two groups and if so, identify them. The Lithuanian sample consisted of 381 children ranging from 6 to 16 years of age. Stratified random sampling was used for the following variables: age, gender, residential area, parent’s (or guardian’s) education level. Scaled scores were assigned to each Lithuanian child using the UK norm tables. The mean differences of WISC-III subtests showed that Lithuanian children received lower scores than the UK sample (p≤0,05). Item analysis showed that some items were too difficult or too easy for Lithuanian children and some items had low discrimination value. This was particularly obvious in the following subtests: Information, Similarities, Arithmetic, Vocabulary, Digit Span and Picture Completion. These subtests were deemed to be culturally specific. The implication of cultural context for the Digit Span subtest is reflected by the difference in the number of syllables digits in English and Lithuanian. It is proposed that some items are not measuring the same thing in the Lithuanian and UK samples. The main conclusion of this study is that the Lithuanian sample results differed from the UK sample and some changes of items and the establishment of Lithuanian norms are recommended.
Keywords: intelligence; WISC-III; testing